Cross-Generational Transmission of Early Life Stress Effects on HPA Regulators and Bdnf Are Mediated by Sex, Lineage, and Upbringing - Coley, Elena J. L.; Demaestri, Camila; Ganguly, Prabarna; Honeycutt, Jennifer A.; Peterzell, Shayna; Rose, Natasha; Ahmed, Nida; Holschbach, Mary; Trivedi, Malav; Brenhouse, Heather C. (Frontiers in Behavioral Neuroscience, 2019)
Early life stress (ELS) is a potent developmental disruptor and increases the risk for psychopathology. Various forms of ELS have been studied in both humans and rodents, and have been implicated in altered DNA methylation, gene transcription, stress hormone levels, and behavior. Although recent studies have focused on stress-induced epigenetic changes, the extent to which ELS alters HPA axis function and stress responsivity across generations, whether these effects are sex-specific, and how lineage interacts with upbringing to impact these effects, remain unclear. To address these points, two generations of rodents were utilized, with the first generation subjected to ELS via maternal separation, and the second to a balanced cross-fostering paradigm. We hypothesized that ELS would disrupt normative development in both generations, manifesting as altered methylation and expression of genes associated with stress signaling pathways (Nr3c1, Nr3c2, and Bdnf), blunted corticosterone (CORT), and anxiety-like behaviors. Additionally, we expected deficits in the second generation to be modulated by caretaking environment and for the pattern of results to differ between the sexes. Results suggest that direct exposure to ELS leads to sex-specific effects on gene regulation and HPA functioning in adulthood, with maternal separation leading to increases in Bdnf methylation in both sexes, decreases in Bdnf expression in females, and decreases in Nr3c1 methylation in males, as well as blunted CORT and less anxiety-like behavior in females. These alterations converged with caretaking to impart perturbations upon the subsequent generation. Across sex, ELS lineage led to decreased methylation of Nr3c1, and increased methylation of Bdnf. In fostered animals, upbringing by a previously stressed mother interacted with offspring lineage to impact methylation of Nr3c1 and Bdnf. Upbringing was also implicated in altered anxiety-like behavior in males, and baseline CORT levels in females. Such effects may correspond with observed alterations in maternal behavior across groups. In conclusion, ELS conferred enduring sex-specific alterations, both first-hand and trans-generationally via both lineage and upbringing. Importantly, lineage of cross-fostered pups was sufficient to normalize or disturb maternal behavior of foster-dams, an observation requiring further elucidation. These results have implications for multi-generational effects of ELS in humans and motivate early interventions.